The proposed design of co-combustion stoker for Şırnak agricultural biomass waste and Şırnak asphaltite in 35mw electricty production - Tosun, Yıldırım İsmail (IJRER, 2015)
The objective of this study is to determine and use the agricultural biomass potential in terms of the types, quantities and regional distribution with Şırnak asphaltite and lignite in Turkey for electricity. The calorific values of the selected agricultural wastes were investigated. It was found that the total calorific value of the studied waste of corn crop field was around 18 kJ /kg. There was 26 million ton total biomass waste production for the period of 2012- 2013 in Turkey. The major waste of crops that took place in the ratio of the total calorific value was corn (43.4 %), wheat (19.6 %), and cotton (16.1 %). The total calorific value of the fruit waste residue was 5 PJ/year. The fruit wastes were major peanut (55.8 %) and olive (25.9 %) in the total agricultural biomass source. The total calorific values for cow, sheep and poultry in Turkey were found to be wastes approximately 4.8, 0.3 and 0.7 PJ/year, respectively.
Keywords: Co-combustion; co-inceneration; Biomass; Agricultural Waste; Co-electiricity